Saudi Oncology Society and Saudi Urology Association combined clinical management guidelines for urothelial cell carcinoma of the urinary bladder - Sultan Alkhateeb; Mubarak Al-Mansour; Mohammed Alotaibi; Ahmad Saadeddin; Ashraf Abusamra; Danny Rabah; Esam Murshid; Abdullah Alsharm; Imran Ahmad; Hussain Kushi; Abdullah Alghamdi; Khalid Alghamdi; et al. (Urology Annals, 2016)
This is an update to the previously published Saudi guidelines for the evaluation, medical, and surgical management of patients diagnosed with urothelial cell carcinoma of the urinary bladder. It is categorized according to the stage of the disease using the tumor node metastasis staging system 7th edition. The guidelines are presented with supporting evidence level, they are based on comprehensive literature review, several internationally recognized guidelines, and the collective expertise of the guidelines committee members (authors) who were selected by the Saudi Oncology Society and Saudi Urological Association. Considerations to the local availability of drugs, technology, and expertise have been regarded. These guidelines should serve as a roadmap for the urologists, oncologists, general physicians, support groups, and health care policy makers in the management of patients diagnosed with urothelial cell carcinoma of the urinary bladder.